Indwelling ureteral stents and sexual health: a prospective, multivariate analysis - Sighinolfi, M C; Micali, S; De Stefani, S; Mofferdin, A; Grande, M; Grande, A; Giacometti, M; Ferrari, N; Rivalta, M; Bianchi, G (The Journal of urology, 2007)
Ureteral stents are common devices in urological practice. However, a stent may provoke lower urinary tract symptoms that severely affect quality of life. We evaluated the relationship between ureteral stents and male erection/female sexuality. A total of 30 men and 20 women undergoing ureteral stent positioning were considered. Patients affected by risk factors for erectile dysfunction or hormonal and metabolic alterations were excluded. Hystero-ovariectomy and menopause were considered exclusion criteria. Three questionnaires were administered before stenting and 45 to 60 days after stent positioning, including the International Prostate Symptom Score, the International Index of Erectile Function-5 for men and the Female Sexual Function Index for women. Mean age was 45 years in men and 39 years in women. The mean+/-SD International Index of Erectile Function-5 score was 23.2+/-1.27 and the mean Female Sexual Function Index score was 32.15+/-2.71 before stent positioning. No lower urinary tract symptoms were reported before the procedure. After the ureteral stent was indwelling the mean International Index of Erectile Function-5 score was 13.5+/-4.01 and the mean Female Sexual Function Index score was 23.6+/-14.66 (p=0.000 and 0.007, respectively). Of 30 men 25 reported a pathological International Index of Erectile Function-5 score and 6 of 20 women denied any sexual activity due to stent related anxiety, resulting in the minimum Female Sexual Function Index score. In the remaining 14 women sexual life was not significantly impaired by the ureteral stent (p=0.08). Ureteral stents impaired the quality of sexual life in male and female subjects. In men the most important distress was in regard to erectile function, probably related to lower urinary tract symptoms. Conversely female sexuality appeared to be severely impaired due to stent related psychological concerns.